Reactivity of [M4(co)12(µ-pyms)4] (M = Mn, re; pymS = pyrimidine-2-Thiolate) with bis(triphenylphosphino)nickel(ii) dicarbonyl: X-ray crystal structure of [Re(Co)3(?2-pymS)(PPh3)] (Journal of Bangladesh Academy of Sciences, 2014)
The reaction between the tetranuclear compound [Mn4(CO)12(µ -pymS)4] (1) and (PPh3)2Ni(CO)2 at room temperature resulted in the cleavage of the square to afford the dinuclear complex [Mn2(CO)5(µ -pymS)2(PPh3)] (2) (19%) along with two mononuclear complexes fac- [Mn(CO)3(?2-pymS)(PPh3)] (3) (43%) and [Mn(CO)2(?2-pymS)(PPh3)2] (4) (24%). In contrast, a similar reaction of [Re4(CO)12(µ-pymS)4] (5) with (PPh3)2Ni(CO)2 at 25oC did not afford any dinuclear compound leading instead to the monophosphine substituted mononuclear compound fac- [Re(CO)3(?2-pymS)(PPh3)] (6) (72%). Compound 4 is also formed when a toluene solution of 3 is treated with PPh3 at elevated temperature (100oC). A similar treatment of 6 with triphenylphosphine in refluxing toluene gave [Re(CO)2(?2-pymS)(PPh3)2] (7) (60%). All the new compounds have been characterized by elemental analysis, IR, 1H NMR and 31P{1H} NMR spectroscopy and mass spectrometry along with single crystal X-ray diffraction analysis for 6. Compound 6 consists of a single rhenium atom with three carbonyls, a triphenylphosphine ligand and a chelating pyrimidinethiolate ligand. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21340 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 155-165, 2014